Motivation and fatigue effects in pupillometric measures of listening effort - Alfandari Menase, Defne (2022)
Listening effort and fatigue are common among individuals with hearing impairment, although within hearing sciences the relationship between effort and fatigue is not fully understood. The objective measurement of listening effort has commonly involved pupillometry in combination with the speech-in-noise paradigm, where the baseline pupil diameter (BPD) is used as a reference point, and the mean and peak pupil dilation (MPD and PPD) as indices of listening effort. Research to quantify listening effort to date has mostly investigated effort as a function of listening demands. Recent research has shown a correlation between PPD and daily-life fatigue. Furthermore, monetary incentives have been shown to increase the PPD, suggesting that listening demands alone are insufficient to explain variation in PPD. How motivation and fatigue influence the pupil metrics remains unclear.